IMPACT OF HEAVY METAL SOIL POLLUTION AND EFFECTS ON HUMAN HEALTH - LEGISLATIVE PROVISIONS - Claudiu-Denis Filip; Mirela Coman (Agricultura)
As regards the research methodology, this paper used the comparative method between the current legislation in force in the Member States of the European Union on regulated standards for heavy metal content in soil.